KONTRIBUSI SISTEM AGROFORESTRI TRADISIONAL DALAM MENDUKUNG EKSISTENSI SOSIAL EKONOMI RUMAH TANGGA (Studi di Desa Sungai Langsat, Kabupaten Banjar) - ASYSYIFA ASYSYIFA (Lambung Mangkurat University-Indonesia, 2011)
ABSTRACT. The Aim of the research was: (1) to study system and process the agroforestry system, (2) to discriptions management system that cover division of labour, in working and work system with the institute, and (3) to observe composition and plants structure with system agroforestry. This object system agroforestry that developed by society at Sungai Langsat village of Banjar Regency in it consist of kind and the composition that form a system. location that be watchfulness object system agroforestry that managed by society at Sungai Langsat village of Banjar Regency. The result was to show garden management agroforestry at Sungai Langsat village, can be taken conclusion as follows: System agroforestry found at Sungai Langsat village consist of one system agroforestry that is system agrisilvicultur with two sub system, that is sub system agroforestry rubber plantation and mixture fruit garden. Process development history it’s for system agroforestry location watchfulness in the begining nature forest and or coppice. Then opened by society for effort arable land plants season. Along with walk it time, besides plant season, also plant fruits plants wood and sap producer plants then in fruits plants the development round into mixture fruit garden form that consist of various fruit tree widespread at random and irregular. While rubber planting inclined planted uniformly and coeval. Management system agroforestry at Sungai Langsat village still has tradisional where the tune position property tune each has by one family he . In this tradisional management system is labour a large part uses labour from family member. In working is begun morning until daytime and evening. Operative institute system stills limit of family member and not yet in the form of formal institute organization. Ecological condition based on conditon vegetasi at tune agroforestry resembles nature forest ecosystem condition with plants kind variety consist from 14 fruit producer plants kinds and 1 sap producer plants kind, vertical structure consists of four stratifications, important value index is dominated kind likes rubber, jackfruit, durian and langsat.Keywords : traditional agroforestry system, contribution, kebun buahABSTRAK. Penelitan ini bertujuan untuk mempelajari : (1) mengetahui kontribusi sistem agroforestri terhadap aspek ekonomi rumah tangga, dan (2) mengetahui nilai sosial sistem agroforestri tradisional bagi petani penerap agroforestry.Lokasi yang menjadi obyek penelitian adalah sistem agroforestri yang dikelola oleh masyarakat di desa Sungai Langsat Kabupaten Banjar. Penelitian ini menunjukkan bahwa sistem agroforestri yang terdapat di desa Sungai Langsat terdiri dari satu sistem agroforestri, yaitu sistem agrisilvikultur dengan dua sub sistem , yakni sub sistem agroforestri kebun karet dan kebun buah campuran. Dari aspek ekonomi kontribusi yang diberikan kebun agroforestri pada pendapatan masyarakat cukup besar, yaitu rata-rata 53,31% dengan pendapatan perkapita sebesar Rp. 5.159.105,- per orang per tahun. Hal ini menunjukkan bahwa kontribusi lahan agroforestri pada pendapatan masyarakat cukup besar, sehingga hasil dari lahan agroforestri tersebut masih bisa diinvestasikan dalam bentuk tabungan yang bermanfaat untuk membangun rumah, membeli kendaraan, biaya perkawinan anak, ibadah haji dan sebagainya.Kata Kunci: sistem agroforestri tradisional, kontribusi